Caracterização de atapulgita visando aplicação para reforço de materiais poloméricos - Costa, Antonio Carlos Silva da (2011)
The clay mineral attapulgite is a group of hormitas, which has its structures formed by microchannels, which give superior technological properties classified the industrial clays, clays of this group has a very versatile range of applications, ranging from the drilling fluid for wells oil has applications in the pharmaceutical industry. Such properties can be improved by activating acid and / or thermal activation. The attapulgite when activated can improve by up to 5-8 times some of its properties. The clay was characterized by X-ray diffraction, fluorescence, thermogravimetric analysis, differential thermal analysis, scanning electron microscopy and transmission electron microscopy before and after chemical activation. It can be seen through the results the efficiency of chemical treatment, which modified the clay without damaging its structure, as well as production of polymer matrix composites with particles dispersed atapugita